Class clown [compact disc, unabridged] : the memoirs of a professional wiseass: how I went 77 years without growing up - Barry, Dave (Simon & Schuster Audio, 2025)
How does the son of a Presbyterian minister wind up winning a Pulitzer Prize for writing a wildly inaccurate newspaper column read by millions of people? Dave Barry takes listeners on a hilarious ride, starting with a childhood largely spent throwing rocks for entertainment and preparing for nuclear war by hiding under a classroom desk. After literally getting elected class clown in high school, he went to college, where, as an English major, he read snippets of great literature when he was not busy playing in a rock band.